Estimating the Employment Effects of Wage Discrimination - Baldwin, Majorie; Johnson, William G. (The Review of Economics and Statistics, 1992)
If labor supply curves are not perfectly inelastic, wage discrimination induces some minority workers to leave the labor force. Studies of discrimination that focus only on wage differentials overlook these disincentive effects on minority employment. This article introduces a method of estimating the employment effects of wage discrimination and applies it to data on men and women from the 1984 Survey of Income and Program Participation. The authors find that wage discrimination against women caused a net loss of over four million jobs, supporting Gary Becker's contention that discriminatory employers use labor inefficiently. Copyright 1992 by MIT Press.